The Association Between Activity-Based Costing And Performance: Empirical Evidence From Moroccan Companies - Karim Charaf; Ahmed Fath-Allah Rahmouni; Mohamed Sabar (Journal of Accounting and Management Information Systems (JAMIS), 2022)
Research Question - Can the adoption of ABC have a positive impact on the performance of the company? Motivation - We have observed in the literature that studies on the impact of ABC on performance most often focus on financial performance. We want to explore this theme by studying, in addition to financial performance, non-financial performance. Idea - This study attempts to study the impact of ABC on performance. Data - Data was gathered using a multi-item questionnaire survey on large companies. To obtain rich data, three semi-structured interviews were conducted with management controllers. In total, 62 companies responded to the questionnaire. Tools - We used two types of tests to analyze the data: the Wilcoxon and Mann-Whitney tests and the median test. Findings - The results indicate that, overall, companies that have adopted ABC have improved their performance significantly. Indeed, its adoption has a positive effect that is more important than the traditional method on the non-financial performance of companies. However, a direct relationship between ABC and financial performance has not been confirmed. Contribution - Previous studies have focused on the effect of ABC on financial performance with inconclusive results. Our contribution has been to demonstrate the positive impact of ABC on non-financial performance. We have also concluded an indirect relationship between ABC and financial performance, which happens precisely through improving non-financial performance. We also concluded the importance of the time variable in evaluating the link between ABC and performance. The expected benefits from ABC depend on time and cannot be delivered immediately and simultaneously.
Keywords: M41; 650; Activity-Based Costing; performance; management accounting; performance dimensions